Evaluating planetary boundary-layer schemes and large-eddy simulations with measurements from a 250-m meteorological mast. Issue 6 (September 2020) - Peña, Alfredo; Hahmann, Andrea N.
Abstract: We evaluate the performance of six planetary boundary layer (PBL) schemes and a large-eddy simulation (LES) for the characterization of the neutral PBL through idealized simulations using the Weather Research and Forecasting model. The evaluation is performed by comparison with sonic anemometer measurements from a 250-m tall meteorological tower that observes close-to-homogeneous winds under the predominant westerlies. All simulations show similar behavior for the vertical temperature profile except for one that uses a non-local PBL scheme, which is known to produce excessive vertical mixing. Within the range of measurements of the tower and except for a PBL scheme that produces a too low jet, the simulations using PBL schemes, which were developed to simulate the nighttime atmosphere, generally show the largest deviations from the observed wind speeds. As expected within the surface layer, the LES shows excessive vertical shear. More importantly, we find that two PBL schemes that use their own surface-layer scheme are effectively reducing the surface roughness. When looking at the vertical profile of momentum exchange coefficient, we find very good agreement between a local and a non-local PBL scheme within the bulk of the PBL, the highest values for the simulation with the PBL scheme showing excessive vertical mixing and the lowest values for that most suitable for nighttime conditions. The comparison with the observed turbulent kinetic energy reveals a good match between the LES and a simulation using a local PBL scheme and a general underestimation (overestimation) of turbulence within the range of measurements by the PBL schemes (LES).